Encyclopedia of Statistics in Quality and Reliability 2007
DOI: 10.1002/9780470061572.eqr439
|View full text |Cite
|
Sign up to set email alerts
|

B ayesian Networks in Reliability

Abstract: Over the last decade, Bayesian Networks (BNs) have become a popular tool for modelling many kinds of statistical problems. We have also seen a growing interest for using BNs in the reliability analysis community. In this paper we will discuss the properties of the modelling framework that make BNs particularly well suited for reliability applications, and point to ongoing research that is relevant for practitioners in reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 21 publications
0
69
0
1
Order By: Relevance
“…In this way, BBN is a graphic representation of a multivariate probability distribution where it is possible to represent cause-effect relations among random variables (Langseth & Portinale, 2007). Moreover, BBNs provide flexibility in terms of knowledge updating through the Bayes theorem (see Bernardo & Smith (1994) for basic concepts on Bayesian inference) as discussed in following section.…”
Section: Bbn Structurementioning
confidence: 99%
See 2 more Smart Citations
“…In this way, BBN is a graphic representation of a multivariate probability distribution where it is possible to represent cause-effect relations among random variables (Langseth & Portinale, 2007). Moreover, BBNs provide flexibility in terms of knowledge updating through the Bayes theorem (see Bernardo & Smith (1994) for basic concepts on Bayesian inference) as discussed in following section.…”
Section: Bbn Structurementioning
confidence: 99%
“…Some recent applications are Langseth & Portinale (2007) in which a modeling framework of reliability and its properties are discussed, and Droguett & Menezes (2007) …”
Section: Bayesian Belief Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…14 While conventional techniques such as fault trees fail to capture this dynamic behaviour, Bayesian belief networks (BBNs) support reasoning under uncertainty and constitute a flexible and powerful probabilistic modelling framework that makes them suitable for applications in the field of reliability and maintenance. 15,16 Recently, influence diagrams and BBNs have been used for modelling the reliability of civil structures. Models have been used to optimize the acquisition of condition data of structures 17 and optimize the maintenance of individual structures.…”
Section: Technology Reviewmentioning
confidence: 99%
“…One such framework for building statistical models for complex systems is the Bayesian network (BN) framework [1][2][3]. BNs have gained popularity over the last decade [4], partly because a number of comparisons between BNs and the classical reliability formalisms have shown that BNs have significant advantages [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%